A Directionality & Novel Function for Stock Price Modelling Prediction Dynamics based on Multiple Learning (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Several methods have been used to forecast stock market movements. However, owing to the complexities of the stock market, the findings are not entirely acceptable. Normally, to deduce a time-scale problem standardized method are taken into consideration. Other techniques followed are mainly lacking behind in terms of distinctive time attributes in the stock dataset as well as the simple and rational concept of the drift. In the study of this paper, we introduce a method to improve prediction accuracy by using the features of the time of the given stock dataset. Firstly, we never treat the data unsystematically, we use the weighted time function accurately to allocate loads to data based on their random proximity to the dataset that is expected. Secondly, concepts of stock patterns were conventionally introduced by citing the monetary thesis and speculations. Time series forecasting can be difficult since there are several methods to choose from, each with its own set of hyperparameters. The Prophet library is a free and open-source library for forecasting univariate time-series datasets. It is simple to use and is intended to automatically find a good collection of hyperparameters for the model in order to make accurate forecasts for data that has patterns and seasonal structure by default. We will use the stock prices of Santander Group, a multinational Spanish financial firm headquartered in Madrid in Spain whose founder is Banco Santander. Furthermore, as the world's 16th largest banking institution, Banco maintains a name in all major money-related centres.